Isolasi, Pemurnian dan Karakterisasi Lipase Bakteri Hasil Skrining dari Tanah Tempat Pembuangan Akhir (TPA) Gunung Tugel Banyumas - Zusfahair, Zusfahair; Setyaningtyas, Tien; Fatoni, Amin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
A bacterial lipase producer was isolated from garbage dump soil and was identified its genus. Lipase was extractedaccording to production time optimized, purified using ammonium sulfate fractionation and gel chromatograph.Determination of enzyme characteristic studied were influence of pH, temperature, various metals to lipaseactivity. The result of this research shows that the genus of isolated bacteria which produced lipase wasAcinetobacter sp., the lipase optimum production time is about 18 hours with the activity is about 115 unit/mL. Thehighest activity of lipase fractionation using ammonium sulfate is about 45% and the highest activity of purifyingwith filtration gel chromatograph column using Sephadex G-150 at 24 th fraction. Lipase from crude extract andpurifying product at this fraction has optimum pH 6 and optimum temperature is about 40 oC. Lipase to be classifiedas metalloenzyme that shows with decreasing the activity after added the EDTA. Metals ion, such as Cu 2+ and Zn2+were inhibited the lipase activity. Ca 2+ ion could increase lipase crude extract activity but inhibited the activity oflipase purifying product. Hg2+ ion could increase the activity of lipase purifying product.